Indications of an Achaea sp. caterpillar outbreak disrupting fruiting of an ectomycorrhizal tropical tree in Central African rainforest - Norghauer, Julian M.; Newbery, David M.; Neba, Godlove A. (Plant ecology and evolution, 2023)
Background and aims – Where one or several tree species come to dominate patches of tropical forest, as many masting ectomycorrhizal legumes do in Central Africa, ecological theory predicts they may be prone to herbivory, which might alter their reproductive output. This was indirectly investigated in lowland rainforest in Cameroon for Tetraberlinia korupensis , whose crowns were attacked in 2008 by an outbreaking black caterpillar—identified as an Achaea sp., probably A. catocaloides —in Korup National Park. Material and methods – Field-collected data on tree-level seed and fruit (pod) production of T. korupensis in its 2008 masting event were compared with that of its two co-dominant neighbours ( T. bifoliolata , Microberlinia bisulcata ), whose populations masted in 2007 (and 2010). To do this, bivariate regression models (linear, polynomial, ZiG [zero-inflated gamma model]), contingency table analysis, and non-parametric measures of dispersion were used. Key results – Assuming T. korupensis is prone to Achaea caterpillar attacks, empirical data support the hypothesized lower proportion of adults participating in its masting (54% in 2008) than for either masting population of M. bisulcata (98% in 2007, 89% in 2010) or T. bifoliolata (96% in 2007, 78% in 2010). These fruiting T. korupensis trees were about one-third larger in stem diameter than conspecific non-fruiters and produced as many pods and seeds per capita as T. bifoliolata . However, regressions only modestly support the hypothesis that the positive tree size–fecundity relationship for T. korupensis was weaker (i.e. lower adj. R 2 ) than for M. bisulcata (whose leaves are morphologically similar) or T. bifoliolata , with mostly similar dispersion about the median among these species. Conclusion – Altogether, the findings suggest a role for tolerance in nutrient-poor forests. It is postulated that instead of conferring resistance to herbivores, the ectomycorrhizas associated with these trees may enable them to more quickly recover from potential yet unpredictable insect outbreaks.